IMPLEMENTASI KEBIJAKAN PENCEGAHAN PERNIKAHAN ANAK MELALUI PROGRAM FORUM ANAK DI KECAMATAN MLATI, KABUPATEN SLEMAN - Ayu Puspitasari, Adelia; Fitri Mutmainah, Nur (Penerbit Lafadz Jaya, 2025)
Child marriage remains a critical issue requiring effective policy implementation. In Illati District, it has the highest number of marriage cases compared to other districts in Sleman Regency. The purpose of this study is to provide solutions and analyze how the implementation of child marriage prevention policies through the child forum program in Mlati District, Sleman Regency is in accordance with Sleman Regent Regulation Number 31 of 2019 concerning the prevention of child marriage using Edward III's theory which has 4 variables, namely communication, resources, disposition, and bureaucratic structure, and to find out the obstacles experienced during the implementation process. This research method uses qualitative descriptive. The results of this study indicate that the implementation of child marriage prevention policies through the child forum program in Mlati District has been effective because there has been socialization to junior high schools and the delivery of educational materials related to the risks of child marriage through podcasts, posters, and peer group discussions. The child forum collaborates with other stakeholders such as DP3AP2KB Sleman, UPT PPA, and psychologists at the Mlati District Health Center by providing guidance to the child forum regarding materials in accordance with its program plan such as child marriage. There are obstacles in budget reductions, unfavorable conditions during socialization to junior high schools, and incomplete members of the children's forum when carrying out activities and meetings. The conclusion of this study is that with the support and guidance from stakeholders, it can help the success of a program carried out by the children's forum in preventing child marriage in Mlati District. The researcher's suggestion is to strengthen the solidarity of the children's forum members so that when running the program or meeting, all can attend. When carrying out socialization, there must be an adult companion or facilitator so that the situation becomes conducive. The children's forum should conduct a survey before and after the implementation of the program to measure changes in perception and attitudes towards child marriage.